Anti-neurodegenerative Activity of Anthocyanin Extract from Endemic Plant Species in the Philippines: A Systematic Review - Lacorte, Laarni Hannah; Asis, Sophia; Buenaventura, Jan Lance; Bulanhagui, Angelic; Male, Reianna Mae; Maniquis, Kristel Faith; Olandez, Joaquin; Samulde, Keneth Dayle; Nas, John Sylvester (Asian Journal of Biological and Life Sciences)
Introduction: Currently, neurodegeneration is increasingly prevalent and proves to be a serious health problem. Plant extraction containing phytochemical compounds that are rich in anthocyanin regulates several factors contributing to neurodegeneration-related conditions and are used to gain greater understanding of these diseases. Aim: Anti-neurodegenerative activity studies have been used in different kinds of anthocyanin-plant cultivated in other countries. The aim of this study was to gain an understanding of anti-neurodegenerative activity of anthocyanin-containing plants found in the Philippines and discover its neuroprotective effect. Methods: The related research and studies are limited within the past 5 years of the review’s submission, anthocyanin-containing plant species in the Philippines, and the records are monitored thoroughly by excluding duplicates and full-text articles were assessed for eligibility. Results: A study showed that a dose of 24mg/kg a day of anthocyanin (ANC) for 2 weeks prevented production of reactive oxygen species (ROS) and inhibited neurodegeneration as well as neuroinflammation in mice by reversing the phosphor-c-Jun N-terminal kinase 1 (P-JNK). Evidences highlight the anthocyanin effectivity in rat models which destabilizes aβ (amyloid beta) by blocking its oligomeric structure formation. The induced metal toxicity, evidence of remyelination and neuron survival by ANC was discovered as well. The related studies reviewed showed relevant findings of anthocyanin content in Philippine plants and their impact in neuroprotection; plants like Bignay (Antidesma bunius) showed 436.602 mg/100 mL, Dragon fruit (Hylocereus spp.) noted 81.75+ 1.43 mg/100g, Rambutan (Nephelium lappaceum l.) Husk showed 393 mg/100g, and lastly Purple yam (Dioscorea alata) with 560 mg/100 g. Conclusion: With the gathered data, this reveals that ANC directly impacts the brain and a number of effectors, including oxidative and nitrosative stress, glial inflammation, protein aggregation, and toxicity.
Keywords: Anthocyanin; Anti-neurodegenerative; Bignay; Dragon fruit; Purple yam; Rambutan